WMS : revenue model innovation for gaming solutions - Sawhney, Mohanbir S.; Goodman, Pallavi; Broit, Ori (London : SAGE Publications Ltd, 2017)
In 2014 WMS Gaming, a manufacturer and seller of slot machines to casinos, was considering a redesign of its existing revenue model. As technology evolved and customer demand for gaming solutions intensified, new and innovative revenue models were being adopted in other technology markets. Most notably, the subscription revenue model, in which customers paid a monthly subscription fee rather than a large upfront fee, was becoming widely adopted in the software industry. Product manager Dayna Stone had the task of evaluating several revenue models and recommending one that most suited WMS's business needs and at the same time took customer needs and wishes into consideration. Complicating this decision were several factors that would have to be kept in mind. Americans' love of gaming had led to a mushrooming of casinos, which meant increased competition for casino dollars. Yet the financial crisis of 2008 and its aftermath had weakened demand for casinos. In addition, casinos, depending on the type of customers they attracted, differed in their appetite for innovation and maintenance of their slot machines. Students will step into the shoes of Dayna Stone as she undertakes the task of weighing these factors and selecting the right revenue model.
Originally published in Sawhney, M., Goodman, P., & Broit, O. (2016). WMS: Revenue model innovation for gaming solutions.5-215-254. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; WMS Gaming; Gambling industry; Strategic planning; Organizational change